Disentangling body image: The relative associations of overvaluation, dissatisfaction, and preoccupation with psychological distress and eating disorder behaviors in male and female adolescents. Issue 2 (19th August 2016) - Mitchison, Deborah; Hay, Phillipa; Griffiths, Scott; Murray, Stuart B.; Bentley, Caroline; Gratwick‐Sarll, Kassandra; Harrison, Carmel; Mond, Jonathan
ABSTRACT: Objective: The distinctiveness and relative clinical significance of overvaluation, dissatisfaction, and preoccupation with body weight/shape remains inconclusive. This study sought to add to the evidence by testing associations between these three body image constructs and indicators of clinical significance. Method: Male and female secondary students ( N  = 1, 666) aged 12–18 years completed a survey that included measures of dissatisfaction with, overvaluation of, and preoccupation with weight/shape, psychological distress, eating disorder behaviors, and basic demographic information. Conditional process analysis was employed to test the independent and mediating effects of overvaluation, dissatisfaction, and preoccupation on distress, dietary restraint, and objective binge eating. Results: Overvaluation, dissatisfaction, and preoccupation were highly correlated ( r  = 0.47–0.84). In girls, preoccupation demonstrated the strongest independent and mediating effects on distress, dietary restraint, and binge eating; whereas neither the direct or indirect effects of dissatisfaction on distress and overvaluation on binge eating were significant. Among boys however, the direct and indirect effects of overvaluation, dissatisfaction, and preoccupation on distress and eating disorder behaviors were relatively equal. Discussion: Preoccupation with weight/shape may be particularly clinically significant in girls, whereas all constructs of body image disturbance may be equally clinically significant in boys. The findings are consistent with the view that these constructs, while closely related, are distinct. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:118–126)